Optimisation of ventilation system of the air-cooled turbo generator - Franc, Jiri; Pechanek, Roman; Kindl, Vladimir (2016 17th International Conference on Mechatronics - Mechatronika (ME), 2016)
This paper deals with optimization of the ventilation system using Computed Fluid Dynamics (CFD). Several analyses were made to figure out the influence of transfer ducts cross section change. It also shows ventilation principals of the tested machine and the particular workflow of this CFD analysis.